A South Indian Subcaste: Social organization and religion of the pramalai kallar - Dumont,Louis (Oxford university press, 1986)
Dumont traces the history and distribution of the Pramalai Kallars of south India: their culture, agricultural practices, economic and political organization, and the collective representations embedded in their social organization and religion.